2001
DOI: 10.1054/bjom.2001.0718
|View full text |Cite
|
Sign up to set email alerts
|

Changing incidence of oral and maxillofacial tumours in East Java, Indonesia, 1987–1992. Part 2: Malignant tumours

Abstract: A total of 2193 tumours of the mouth and jaw diagnosed at the Laboratorium Patologi Anatomi Fakultas Kedokteran Universitas Airlangga, Indonesia from 1987 to 1992, inclusive, was studied. Malignant tumours constituted 45.3% of the lesions. Almost 71% of the malignant tumours were squamous cell carcinomas. The remainder were salivary gland tumours (21.5%) and sarcomas (4.5%). The male to female ratio for malignant tumours was 5.1:4.7. The incidence of malignant tumours per 100,000 population over the 6-year stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 4 publications
0
10
0
Order By: Relevance
“…Rhabdomyosarcomas appeared to be the most common oral soft tissue malignancy in majority of the geographic regions. Of note, the study by Budhy et al () deviated from this trend and oral SCCs were reported to be most common malignancy in children. The authors proposed that the low social economic status and poor nutritional status of the East Javan population may have contributed to this finding but this was not specific to children.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Rhabdomyosarcomas appeared to be the most common oral soft tissue malignancy in majority of the geographic regions. Of note, the study by Budhy et al () deviated from this trend and oral SCCs were reported to be most common malignancy in children. The authors proposed that the low social economic status and poor nutritional status of the East Javan population may have contributed to this finding but this was not specific to children.…”
Section: Discussionmentioning
confidence: 89%
“…Other reasons included non‐oral or unclear cancer diagnosis terminology ( N = 9) or the full text was unavailable or not retrievable ( N = 3). Fourteen studies were retained, and all were based on biopsy data (Abiose, Ogunniyi, & Oyejide, ; Adebayo, Ajike, & Adekeye, ; Al‐Khateeb, Al‐Hadi Hamasha, & Almasri, ; Aregbesola, Ugboko, Akinwande, Arole, & Fagade, ; Arotiba, ; de Arruda et al, ; Budhy, Soenarto, Yaacob, & Ngeow, ; Creath, Cutter, Bradley, & Wright, ; Effiom et al, ; Iatrou, Theologie‐Lygidakis, Tzerbos, & Schoinohoriti, ; Mohtasham, Saghravanian, Goli, & Kadeh, ; Piloni, Molina, & Keszler, ; Sato, Tanaka, Sato, & Amagasa, ; Trobs, Mader, Friedrich, & Bennek, ).Stratifying by WHO geographic regions, five studies were from the African region (Abiose et al, ; Adebayo et al, ; Aregbesola et al, ; Arotiba, ; Effiom et al, ), three from the Americas (de Arruda et al, ; Creath et al, ; Piloni et al, ), two each from the Eastern Mediterranean (Al‐Khateeb et al, ; Mohtasham et al, ) European (Iatrou et al, ; Trobs et al, ) and South‐East Asia/Western Pacific regions (Budhy et al, ; Sato et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…TCL are malignant proliferations of mature T cells and often associated with an aggressive behavior [8]. TCL primarily presenting in the head and neck region are rare and the incidence ranges from 1 to 17% in various countries with limited information in the Western World [9][10][11]. Extranodal TCL in head and neck region can develop as a primary lymphoma, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Depending on the point in time and the country the study was conducted in, the proportion of lymphomas in the entire field of head and neck malignancies ranges from 1 to 17% 7 , 8 . Surprisingly, little information is available for Western countries, and it is out of date.…”
Section: Introductionmentioning
confidence: 99%